2017
DOI: 10.1016/j.molcel.2017.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Delta-Secretase Phosphorylation by SRPK2 Enhances Its Enzymatic Activity, Provoking Pathogenesis in Alzheimer’s Disease

Abstract: Summary Delta-secretase, a lysosomal asparagine endopeptidase (AEP), simultaneously cleaves both APP and Tau, controlling the onset of pathogenesis of Alzheimer’s disease (AD). However, how this protease is post-translationally regulated remains unclear. Here we report that Serine-arginine protein kinase 2 (SRPK2) phosphorylates delta-secretase and enhances its enzymatic activity. SRPK2 phosphorylates serine 226 on delta-secretase and accelerates its autocatalytic cleavage, leading to its cytoplasmic transloca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 44 publications
4
48
1
Order By: Relevance
“…Accordingly, we also found that microglia, the resident macrophage cells of the brain, express more AEP than neurons and mostly contain the active form of the enzyme. While aberrant AEP activity in neurons has been reported under special conditions (14, 31), we do not observe AEP-mediated tau cleavage in iPS-derived neurons. Even after endocytotic uptake of recombinant tau, which delivers tau directly to endolysosomes and should thus make it available for AEP cleavage (4, 10), we do not observe appreciable amounts of tau 168-368 fragments, suggesting that this proteolytic event is not primarily taking place in neurons.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…Accordingly, we also found that microglia, the resident macrophage cells of the brain, express more AEP than neurons and mostly contain the active form of the enzyme. While aberrant AEP activity in neurons has been reported under special conditions (14, 31), we do not observe AEP-mediated tau cleavage in iPS-derived neurons. Even after endocytotic uptake of recombinant tau, which delivers tau directly to endolysosomes and should thus make it available for AEP cleavage (4, 10), we do not observe appreciable amounts of tau 168-368 fragments, suggesting that this proteolytic event is not primarily taking place in neurons.…”
Section: Discussioncontrasting
confidence: 92%
“…AEP is a lysosomal enzyme that requires a low pH for activation (13). Although cytoplasmic activity has been demonstrated under certain conditions (14), it is mostly described for its role in the endolysosomal system of dendritic cells (15). The activity of AEP in the brain increases with age and is also elevated in AD, leading to the cleavage of additional disease proteins such as amyloid precursor protein (APP) or α-synuclein (12, 16).…”
Section: Introductionmentioning
confidence: 99%
“…This fast ADAM17 activation also occurs for a physiological process called transactivation, in which agonists of G protein‐coupled receptors indirectly activate the EGFR (Prenzel et al , ; Maretzky et al , ). Although this fast activation appears to be independent of phosphorylation of ADAM17 itself, other sheddases can be regulated by direct phosphorylation as observed for the δ‐secretase legumain (Wang et al , ). Another mechanism that is increasingly linked to the shedding control is calcium signaling, as observed for human meprin β (Arnold et al , ) or certain rhomboid proteases (Baker & Urban, ).…”
Section: Regulation Of Sheddingmentioning
confidence: 92%
“…Our findings propose a key role for SRPK in regulating developmental processes, although functional redundancy within the mammalian SRPK family has precluded genetic interrogation of SRPK functions during development; therefore conditional and tissue-specific mouse models of SRPK deletion and inactivation will shed light on the developmental events that are controlled by the SRPK. Nevertheless, SRPK2 is highly expressed in brain (Wang et al, 1998) and regulates processes relevant to neurodegeneration (Hong et al, 2012;Wang et al, 2017), suggesting a role for SRPK in development and maintenance of the nervous system. Furthermore, an siRNA screen indicates SRPK2 is required for efficient X chromosome inactivation (Chan et al, 2011), which is a key developmental function of RNF12.…”
Section: Discussionmentioning
confidence: 99%
“…SRPKs phosphorylate Ser-Arg rich splicing factors, thereby modulating sub-cellular localization, spliceosome assembly and mRNA splicing (Cao et al, 1997;Koizumi et al, 1999;Mathew et al, 2008;Xiao and Manley, 1997). Few non-splicing functions of SRPKs have been reported (Hong et al, 2012;Wang et al, 2017), and it remains unclear whether SRPKs have evolved further complex regulatory roles in metazoans. However, SRPK family members exhibit highly tissue-specific expression profiles (Nakagawa et al, 2005; Wang et al, SRPKIN-1 (Hatcher et al, 2018) (Figure 1A).…”
Section: Introductionmentioning
confidence: 99%